2022
DOI: 10.3390/genes13060986
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Potential Meat Quality Trait Loci in Ducks

Abstract: With continuously increasing living standards and health requirements of consumers, meat quality is becoming an important consideration while buying meat products. To date, no genome-wide association study (GWAS) for copy number variants (CNVs) and single nucleotide polymorphisms (SNPs) has been conducted to reveal the genetic effects on meat quality in ducks. This study analyzed the phenotypic correlation and heritability of fat, water, collagen, and protein content of duck breast muscle. To identify the cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The coiled-coil serine rich protein 1 or CCSER1 gene on OAR6, which encodes a proline-rich protein, plays an important role in mitosis and cell division and has been linked to several human cancers [ 125 ]. SNPs in the intronic region of this gene have been associated with male fertility traits in sheep, such as ejaculate quality [ 126 ], and together with the TIGD2 gene with growth and carcass traits in cattle [ 127 ], body weight in salmon [ 128 ], and meat quality traits in ducks [ 129 ]. The TIGD2 gene has also been associated with resistance to disease and bacterial infection in cattle [ 85 ], making it an important candidate in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The coiled-coil serine rich protein 1 or CCSER1 gene on OAR6, which encodes a proline-rich protein, plays an important role in mitosis and cell division and has been linked to several human cancers [ 125 ]. SNPs in the intronic region of this gene have been associated with male fertility traits in sheep, such as ejaculate quality [ 126 ], and together with the TIGD2 gene with growth and carcass traits in cattle [ 127 ], body weight in salmon [ 128 ], and meat quality traits in ducks [ 129 ]. The TIGD2 gene has also been associated with resistance to disease and bacterial infection in cattle [ 85 ], making it an important candidate in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, newly developed biotechnologies can greatly advance this field: (1) Omics analyses could help identify sex-associated genes and explore their regulation mechanism at various levels. (2) Genomewide association studies (GWASs) could establish the relationships between special traits (such as sex) and genes (or SNPs) through re-sequence analyses [43,44]. (3) The CRISPR system can contribute to gene function characterization through gene gain (or loss) of function [45].…”
Section: Future Investigations Of Gjsox9 In G Japonicusmentioning
confidence: 99%
“…Based on the maturity of sequencing technologies, diverse genomic studies have been performed to identify genomic loci affecting meat quality in pigs. Especially, several population-level studies using short read data, such as population genomic analyses [ 5 7 ] and genome-wide association studies [ 8 10 ], have identified plentiful regions and genes associated with the traits at the whole-genome level.…”
Section: Introductionmentioning
confidence: 99%